Early Clinical Outcomes of Polydioxanone Mesh for Prepectoral Prosthetic Breast Reconstruction. Issue 1 (26th January 2022) - Qiu, Cecil S.; Seth, Akhil K.
Abstract : Background: Many biologic matrices and synthetic meshes are available as adjuncts for prosthetic and autologous breast reconstructions to help control implant position and to reinforce abdominal flap donor sites. Absorbable synthetic meshes may have advantages over biologic matrices and permanent meshes, such as lower cost and better long-term biocompatibility. We present a prospective case series of patients undergoing two-stage, prepectoral breast reconstruction with polydioxanone (PDO) mesh. Methods: This prospective, consecutive single-surgeon series of patients who received PDO mesh during two-stage, prepectoral breast reconstruction involved incorporation of the PDO mesh at stage 1 as an anterior tarp over the tissue expander. A detailed description of surgical technique is provided herein. Surgical complications monitored included surgical site infection, wound dehiscence, mastectomy skin flap necrosis, hematoma or seroma requiring operative intervention, and reconstructive failure. Results: Seven patients with fourteen breast reconstructions were included in the study. All patients had unilateral cancer and underwent bilateral mastectomies with immediate reconstruction. The average age of patient was 50.0 (SD 7.4) and BMI was 29.3 (SD 2.7). Patients were followed for a median of 274 days, during which only one late infection (7.1%) occurred requiring expander removal. Conclusions: PDO mesh has an acceptable short-term complication rate in two-stage prepectoral prosthetic breast reconstruction. Future investigations should elucidate its comparative efficacy and safety against alternative products with respect to long-term outcomes.